Interdisciplinary Diagnosis and Management of Colorectal Cancer for Nursing, Radiology, Laboratory, Nutrition, and Health Informatics Professionals - Almazrou, Naif Hassan; Sharahily, Emad Alawy; Alomran, Amal Abdullah Ali; Alsubhi, Samer Olaythah Ahmed; Alsamy, Samy Fhaid Sulaiman; Yousef, Atiaf Fatehaldein Ali; Mobarki, Fatemah Hassan; Amri, Mansour Ahmed Salman; Aldosari, Manal Abdullah Ali; Albishi, Zainab Abdullah Saleh; Buayti, Meaad Ali Mohammed (Saudi Journal of Medicine and Public Health, 2025)
Colorectal cancer (CRC) remains a significant global health burden, ranking as the third most commonly diagnosed malignancy and the second leading cause of cancer-related mortality worldwide. The complex molecular landscape, heterogeneous presentation, and multifaceted treatment approaches necessitate a collaborative, interdisciplinary framework for optimal patient outcomes. This comprehensive review synthesizes current evidence on CRC pathophysiology, risk factors, diagnostic modalities, and therapeutic strategies while emphasizing the critical roles of nursing, radiology, laboratory medicine, and health informatics professionals in the multidisciplinary care team. Recent advances in genomics, epigenetics, metabolic reprogramming, and artificial intelligence have revolutionized CRC diagnosis and management, creating both opportunities and challenges for healthcare professionals across specialties. The integration of molecular biomarkers, advanced imaging techniques, patient-derived organoids, and computational approaches has enabled more precise risk stratification, early detection, and personalized treatment selection. However, disparities in screening participation, healthcare access, and implementation of novel technologies persist. This review provides a framework for interdisciplinary collaboration, highlighting how nursing professionals can optimize patient education and supportive care, radiology experts can enhance diagnostic accuracy through advanced imaging and radiomics, laboratory specialists can facilitate molecular characterization and biomarker-guided therapy, and health informatics professionals can leverage artificial intelligence and data integration to improve clinical decision-making. By fostering effective communication and coordinated care across disciplines, healthcare systems can address the multifaceted challenges of CRC management and improve patient outcomes.